Potensi Konsep Matematika dalam Penggunaan Aperture di Fotografi - Dona Fitriawan; Islami, Nabillah Jihan; Rifat, Mohamad; Suratman, Dede; Hartoyo, Agung (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to help understand how the use of aperture works with mathematical concepts so that the use of this method is applied to photography activities and as a medium for learning mathematics in schools. The method used in this study is descriptive with the form of action research, because this study describes the mathematical concepts contained in the use of aperture in photography. From the interview, researchers collected information on mathematical concepts contained in the sequence located behind the F-stop number and explored the relationship between the F-stop number and the diameter of the circular aperture opening area in the lens, there are several mathematical concepts such as fractional numbers, geometric series, scales, comparisons, magnitudes & units, space builds, to the area of a circle. In this case, it proves that in the use of Aperture in photography, there are mathematical concepts related to school mathematics learning